DESIGN AND DEVELOPMENT OF HUB AND NACELLE STRUCTURE STRUCTURES FOR WIND TURBINE APPLICATIONS - firmansyah, hendrix noviyanto; sudarmanto, Sudarmanto sudarmanto (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Wind turbine is one of the technology to produce elctricity. Wind turbine consists of wind blade, nacelle, hub and tower. Hub is the structure which connect wind blade to the shaft of the generator to generate electricty.Nacelle is the structure that cover the generator from its environment. Nacelle is not design for strength, so there in no stress analysis for this structure. The purpose of this research is to design and make prototype for hub and nacelle. There are three models for hub, slot model (2 design) and lap joint design, and 1model for nacelle design. hub is selected by the simplicity of process of production and assembly, and by stress analysis. Then the lap joint design is the selected one, so that will be make for prototype. The prototype is made of composite sandwich structure, which is teak wood as its core. The composite sandwich structures is designed for its stiffness criteria.